2018
DOI: 10.11607/prd.2995
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Adaptation and Fracture Resistance of Lithium Disilicate Laminate Veneers on Teeth with Different Preparation Depths

Abstract: The purpose of this study was to evaluate the marginal adaptation and fracture load of ceramic laminate veneers on teeth with different preparation depths. A total of 75 extracted intact human maxillary central incisors were prepared with three different preparation depths (P) and assigned to the following five groups (n = 15): P1 (0.3-mm depth of preparation; preparation entirely in enamel); P2 (0.5-mm depth of preparation; preparation in enamel and dentin complex); P3 (1-mm depth of preparation; preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 11 publications
2
21
0
5
Order By: Relevance
“…In the current investigation, natural teeth were used to furnish a more clinically pertinent substrate with respect to preparation design, bonding protocol, and adhesive cementation that could affect the marginal fit and load to fracture values of monolithic zirconia laminate veneers 33,35) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current investigation, natural teeth were used to furnish a more clinically pertinent substrate with respect to preparation design, bonding protocol, and adhesive cementation that could affect the marginal fit and load to fracture values of monolithic zirconia laminate veneers 33,35) .…”
Section: Discussionmentioning
confidence: 99%
“…2). Each site was measured three times, and a mean value was calculated [33][34][35] . By calculating the mean values of the measurement areas in this manner, the total mean of incisal, axial, and marginal discrepancy values were recorded.…”
Section: Cementation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if such a preparation design is chosen, ceramic thickness at the palatinal site should be increased (for leucitereinforced glass ceramic) to more than 0.5 mm. In vitro studies have also shown that the fracture resistance of laminate veneers with 0.5-mm preparation depth was greater than that of the 0.3-mm and 1-mm preparation depth [25], which, however, for the 1 mm thickness may have been due to the fact that the preparation mainly exposed dentin. It is generally accepted that the preparation should be kept -as much as clinically possible -to the enamel as bonding substrate and over-contour of the veneer should be avoided.…”
Section: Ceramic Thicknessmentioning
confidence: 99%
“…Changes in color and/or position of the anterior teeth may be limiting factors of this approach, often needing greater dental wearing and thicker crowns for adequate solutions 3 . The stability of color and marginal adaptation are essential to a successful esthetic rehabilitation 4 , favorable results in terms of marginal adaptation of ultra thin laminates are described in literature 5 .…”
Section: Introductionmentioning
confidence: 99%